1971
DOI: 10.1302/0301-620x.53b3.510
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Spontaneous and Simultaneous Rupture of the Quadriceps Tendons in Gout

Abstract: 1. A case of bilateral spontaneous and simultaneous rupture of the quadriceps tendons is described. 2. The underlying cause was found to be gouty affection of the tendons. 3. So far as is known, a similar case has not previously been recorded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0
3

Year Published

1972
1972
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(39 citation statements)
references
References 4 publications
1
35
0
3
Order By: Relevance
“…The weakening of the tendon is caused by fibrinoid necrosis with the chronic inflammatory reaction [6,8,15]. When fibrinoid degeneration occurs in the ligamentous or tendinous structure with inflammatory cells, some vessels are thrombosed.…”
Section: Discussionmentioning
confidence: 99%
“…The weakening of the tendon is caused by fibrinoid necrosis with the chronic inflammatory reaction [6,8,15]. When fibrinoid degeneration occurs in the ligamentous or tendinous structure with inflammatory cells, some vessels are thrombosed.…”
Section: Discussionmentioning
confidence: 99%
“…Degenerative changes associated with ageing and calcific tendinopathy have also been shown to be a factor with QT ruptures [3][4][5] . Conditions such as diabetes, chronic renal failure 6 , gout 7 , and quinolone antibiotic use 8 amongst others have been shown to increase the risk of QT ruptures. Prompt surgical repair has been shown to result in good to excellent range of motion, and a return to sport in most studies.…”
Section: Introductionmentioning
confidence: 99%
“…Degenerative changes associated with ageing and calcific tendinopathy have also been shown to be a factor with QT ruptures 3,4 . Spontaneous QT ruptures have been shown to be associated with predisposing conditions such as diabetes, chronic renal failure 5 , gout 6 , and quinolone antibiotic use 7 amongst others. It has also been suggested that the presence of a patella spur, a bony prominence at the QT tendon insertion point of the proximal pole may be associated with ruptures ( Fig.…”
Section: Introductionmentioning
confidence: 99%